Analysis Of The Islamic Legal Paradigm In Studying Monogamy, Polygamy And Divorce - Chifa Azyana Adly Meknesya; Muhammad Hidayat (Program Pascasarjana UIN Sumatera Utara Medan, 2021)
This article examines contemporary Islamic legal perspectives on monogamous and polygamous marriages, as well as the processes and underlying reasons for divorce within the framework of modern Islamic jurisprudence. In everyday life, marital relationships frequently encounter various social, economic, and emotional challenges, prompting individuals to navigate between monogamy as the ideal normative model and polygamy as a conditionally permissible practice under sharia. At the same time, divorce emerges as a complex phenomenon influenced by multiple factors, including incompatibility, economic hardship, and moral considerations. The study aims to explore the views, arguments, and proposed solutions of contemporary Islamic scholars in addressing these issues. Employing a qualitative bibliographic approach, this research draws upon classical fiqh literature alongside the interpretations and analyses of modern scholars, thereby bridging traditional doctrines with current socio-cultural realities. This method allows for a comprehensive understanding of how Islamic legal thought evolves in response to changing contexts. The findings reveal that contemporary Islamic law promotes a balanced, just, and context-sensitive approach to marital issues. Monogamy is strongly encouraged as the ideal form of marriage due to its alignment with principles of fairness and stability. Polygamy, while permitted, is strictly regulated and only justified under compelling circumstances, with the absolute requirement of justice among spouses. Furthermore, divorce is regarded as a last resort, permissible only after all efforts toward reconciliation, mediation, and mutual understanding have been thoroughly exhausted.